Factors associated with PPSV23 coverage among older adults in Japan: a nationwide community-based survey - Yoshitaka Murakami; Shinichi Kanazu; Tanaz Petigara; Mari Saito Oba; Yuji Nishiwaki; Akira Watanabe (BMJ Open)
Objectives The 23-valent pneumococcal polysaccharide vaccine (PPSV23) was included in Japan’s national immunisation programme for older adults in 2014. While vaccination coverage has increased following the implementation of the national immunisation programme, little is known about the factors that have influenced changes in PPSV23 uptake in Japan. This study aimed to investigate the effects of municipality-level activities implemented to improve vaccine uptake during the fiscal year 2015 (April 2015–March 2016).Design Community-based national survey. A postal and web-based nationwide survey was sent to all municipalities in Japan in June 2016 (n=1741). The survey included questions regarding PPSV23 coverage, out-of-pocket costs by individuals for vaccination and community-level activities implemented to improve and promote PPSV23 uptake. Municipality-level and prefecture-level variables (eg, unemployment rates, average per capita income) retrieved from published sources were also incorporated to explore the impact of social determinants on vaccine uptake.Setting Japan.Participants Municipal vaccination officers.Primary and secondary outcome measures The primary study outcome was PPSV23 coverage among adults aged 65 years in Japanese municipalities.Results A total of 1010 municipalities (58.0%) responded to the survey. The median PPSV23 coverage among responding municipalities was 41.8%. Vaccine coverage increased by 18.7% (16.7%–20.7%)%) in municipalities that sent a direct mail notification to the target population of adults compared with municipalities that did not send any notification. Vaccine coverage decreased by 3.02% (2.4%–3.6%)%) for every 1000 JPY increase in out-of-pocket costs. Municipality-level unemployment rates and average per capita income were negatively associated with PPSV23 coverage.Conclusions This nationwide survey provides insight into factors that may influence PPSV23 coverage in Japanese municipalities. Reduced out-of-pocket costs and direct mail notifications to the target population were associated with higher PPSV23 coverage in Japanese municipalities.